Economic effects of the use of mountain pastures for breeding of heifers - Ivanović, Sanjin; Bratić, Siniša; Marković, Todor (Economics of Agriculture, 2010)
In the Republic of Serbia, pastures cover more than 800,000 ha, while pastures and meadows together cover 1,428,000 ha, i. e. 27. 97% of the total exploited agricultural land. However, economic effects of their utilization so far have not been sufficiently explored. The above mentioned areas can be successfully utilized for growing of heifers. Therefore, this paper lists the advantages and economic effects of the use of pastures for breeding of heifers. Using the example of a family farm that utilizes modern technical and technological solutions in accommodating and feeding the cattle, it was determined that the costs of breeding reduce by 19. 07% when exploiting pastures, compared to stable breeding. Different types of cooperation among the cattle farms are proposed particularly focusing on formation of farms specialized in breeding of heifers. Also, the paper lists the problems linked to the utilization of pastures, as well as measures that could contribute to their more effective use.